Socio-Economic Analysis of Hybrid Rice Variety “OPTIMA” Farming in District of Banyuwangi to Increase Income, Indonesia - Syamsul Hadi; Insan Wijaya; Henik Prayuginingsih (Budapest International Research and Critics University, 2018)
In general, hybrid rice has a significant advantage over inbred rice, such as higher yields, more competitive harvesting, wider, shorter plant life, wider photosynthetic area, lower respiratory intensity and higher assimilation translocation . Although in Indonesia hybrid rice has been popularized since 1983, but the empirical facts show that few farmers are adopting new technology in this field of seed, although the price of production is more expensive than the price of the rice product inbrid. Therefore, this paper explains the following matters: 1) Socio-economic factors that influence farmers' decision to plant hybrid rice OPTIMA, 2) Level of profit of hybrid rice farming OPTIMA, and 3) Cost efficiency level of rice farming hybrid OPTIMA. The research method used is descriptive method of quantitative and qualitative techniques where census data information collected includes primary data and secondary data. The population in this research is farmers of hybrid rice varieties of OPTIMA in Banyuwangi. Data analysis techniques used are probability probability analysis of probit model function, cost efficiency analysis, and profit. Simultaneously there are several factors that are expected to significantly influence farmers' decision to plant hybrid rice optima at a 1% significance level. But partially only factor of production amount which have no significant effect to dependent variable (Farmer's Decision, while variable of output price and farmer perception about hybrid varieties of Optima hybrid is significant effect) Farm profit rate during second rainy season and drought in year 2013/2014 reach IDR 9.61.992,06 per hectare with average production of 5,9 tons and the farming efficiency level reached 1,5 or has reached the point of technical efficiency.